Moscow never sleeps [videorecording (DVD)] - O'Reilly, Johnny; O'Reilly, Johnny; O'Reilly, Johnny; Shalonko, Anastasiya; Stoi͡anov, I͡Uriĭ; Serebri͡akov, Alekseĭ, 1964- (Indican Pictures, 2019)
Follows the interconnected stories of five people over the course of a day during the Moscow City Day celebrations.